Acute exercise impairs social-cognitive abilities in children with Autism Spectrum Disorder - Sebastian Ludyga; Fabienne Bruggisser; Rahel Leuenberger; Markus Gerber; Uwe Pühse; Manuel Mücke (Bern Open Publishing, 2023)
Background While children with Autism Spectrum Disorder show heterogeneous cognitive profiles, they share common deficits in social-cognitive abilities and executive function. Moderate endurance exercise is known to elicit changes in the psychophysiological state, which can translate into immediate, but transient benefits for both cognitive domains. However, the cognitive response of children with Autism Spectrum Disorder to acute exercise remains unclear. We addressed this research deficit by investigating the effects of a single endurance exercise session on face recognition abilities and affective response inhibition. Methods We recruited 30 children with Autism Spectrum Disorder aged 7 to 12 years from local clinicals in Basel, Switzerland and via social media. Using a randomized cross-over design, participants completed a moderately-intense, 20-min exercise session on a cycling ergometer and control condition, which involved sitting on the ergometer. We collected heart rate and ratings of perceived exertion during these sessions. Before and after the experimental conditions, participants completed two computerized cognitive tasks. During the Mooney Face Recognition task, they had to categorize stimuli into faces and objects. In the affective Go/NoGo task, participants were instructed to inhibit their response to either sad or happy faces and press a button to all other faces. Results The experimental manipulation was successful as a main effect of condition indicated a higher heart rate and rating of perceived exertion in the exercise compared to the control condition. With regard to cognitive performance, the repeated measures ANOVA revealed an interaction of time and condition for the Mooney Face Recognition task, indicating an increase in reaction time in the exercise compared to the control condition. In contrast, no interaction of time and condition was found for accuracy on this task as well as accuracy and reaction time on the affective Go/NoGo task. Conclusion In children with Autism Spectrum Disorder, a single exercise does not seem to benefit social-cognitive abilities and executive function temporarily. A short cycling bout rather impairs the ability to recognize faces, suggesting that the maintenance of supervised exercise demands a set of joint resources. As these results are in conflict with the well-documented benefit of acute exercise in healthy populations, the atypical cognitive response in children with Autism Spectrum Disorder indicates a moderating role of this neurodevelopmental condition.